Plant–pollinator networks in semi‐natural grasslands are resistant to the loss of pollinators during blooming of mass‐flowering crops. Issue 1 (6th April 2017) - Magrach, Ainhoa; Holzschuh, Andrea; Bartomeus, Ignasi; Riedinger, Verena; Roberts, Stuart P. M.; Rundlöf, Maj; Vujić, Ante; Wickens, Jennifer B.; Wickens, Victoria J.; Bommarco, Riccardo; González‐Varo, Juan P.; Potts, Simon G.; et al.
Abstract : Mass‐flowering crops lead to spatial redistributions of pollinators and to transient shortages within nearby semi‐natural grasslands, but the impacts on plant–pollinator interactions remain largely unexplored. Here, we characterised which pollinator species are attracted by oilseed rape and how this affected the structure of plant–pollinator networks in nearby grasslands. We surveyed 177 networks from three countries (Germany, Sweden and United Kingdom) in 24 landscapes with high crop cover, and compared them to 24 landscapes with low or no oilseed rape during and after crop blooming. On average 55% of grassland pollinator species were found on the crop, which attracted 8–35% of individuals away from grasslands. However, networks in the grasslands were resistant to these reductions, since mainly abundant and highly mobile species were attracted. Nonetheless, simulations indicated that network structural changes could be triggered if > 50% of individuals were attracted to the crop (a value well‐above that found in our study system), which could affect community stability and resilience to further disturbance.